2022
DOI: 10.1007/s12020-022-03016-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-25 and miR-92b regulate insulin biosynthesis and pancreatic β-cell apoptosis

Abstract: Purpose. -Pancreatic β-cell failure is a central hallmark of the pathogenesis of diabetes mellitus; however, the molecular basis underlying chronic in ammation-caused β-cell failure remains unclear. This study reported here speci cally assessed the association between miR-25/miR-92b family and β-cell failure in diabetes.Methods. -IL-1β and two additional ER stress activators, palmitate and tunicamycin were applied to evaluate the expression level miR-25 by Taqman ® RT-PCR. Glucose-and potassium-stimulated insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…miRNAs are involved in various physiological and pathological processes, including differentiation, inflammation, and apoptosis. [47,48] Different studies have suggested that miRNAs play key roles in the progression and inhibition of diabetes-induced organ damage. [49,50] To be more specific, miR-146 mediates many innate and adaptive immune and inflammatory responses in the body.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are involved in various physiological and pathological processes, including differentiation, inflammation, and apoptosis. [47,48] Different studies have suggested that miRNAs play key roles in the progression and inhibition of diabetes-induced organ damage. [49,50] To be more specific, miR-146 mediates many innate and adaptive immune and inflammatory responses in the body.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 39 miR-25 Its overexpression leads to inhibition of insulin biosynthesis and increased β-cell apoptosis. 27 miR-26 Reduces insulin promoter activity and insulin mRNA levels and consequently insulin content. 33 , 39 miR-29 family Its overexpression negatively affects GSIS and β-cell proliferation.…”
Section: The Role Of Mirnas In the Pathogenesis Of Type 2 Diabetesmentioning
confidence: 99%
“… 26 miR-92b Its overexpression leads to inhibition of insulin biosynthesis and increased β-cell apoptosis. 27 miR-96 Represses β-cell function. 38 miR-124a Promotes β-cell dysfunction and death.…”
Section: The Role Of Mirnas In the Pathogenesis Of Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-ethnic miRNA variants have been reported to be associated with regionally distributed diabetes; for example, miR-196a and miR-423 variants have been observed in T2DM patients in Saudi Arabia ( 88 ). Some miRNAs have been observed to be elevated during the development of DM, such as miR-25 and miR-92b ( 89 ). In general, these miRNAs with elevated expression promote the development of DM and play a role in the body’s IR, damage to β-cells, and other processes central to the development of diabetes.…”
Section: Ncrnas In Diabetesmentioning
confidence: 99%